Sound Similar in Surat Poets - سارة محمد عبد الجبار (College of Education for Women, 2019)
This research deals with the phenomenon of a similar voice phenomenon has founded its own laws similar and includes the following phenomenon: Azahrh aledgam: and Qdbent Tarifaoshrooth or dinaces and reflects the correlation between language and reading and then apply the provision in sura blessed. Phenomenon Alaalal and substitution, Two of the important acoustic phenomenon the linguistic heritage has shown Alaalal types and the difference between him and the substitution then counted their applications in Sura. Similar phenomena: in name and deed shares bult causes and probability voices and sound that refrais where tilt.